Time Series Analysis of The Impact of Consumption and Energy Use on Environmental Degradation: Evidence from Malaysia - R. Ratneswary V. Rasiah,; Baharom Abdul Hamid,; Wilson Ow Chee Seong,; Muzafar Shah Habibullah, (Kajian Malaysia, 2015)
The purpose of this study is to explore the long-run relationships and short-run dynamic interactions between environmental degradation (proxied by carbon dioxide, CO2 emissions) and the independent variables of consumption (proxied by income level or gross domestic product, GDP per capita) and energy use in Malaysia over the period 1971 to 2008, using time-series analysis. The multivariate cointegration methodology is applied in this study to establish the possible causal relations between the variables concerned. The cointegration test and the vector error correction model display the evidence of a positive long-run relationship between consumption and environmental degradation while energy use is negatively related to environmental degradation. The long-term elasticity coefficients of the exploratory variables on environmental degradation display relationships that are theoretically grounded. There is evidence that consumption and energy use have a dominant influence in forecasting environmental degradation variance through further innovation analysis using variance decompositions. The study concludes with an examination of policy implications of the findings.